Pig meat quality from entire males - K. Lundström; K.R. Matthews; J.-E. Haugen (Animal, 2009)
This paper constitutes an updated review of the production and meat quality aspects of rearing entire male pigs. Since a major obstacle in rearing entire males is the incidence of boar taint, possible methods for detection are also summarised. Safe and fast methods for detection of boar taint would be valuable in avoiding complaints from consumers. Pig meat quality is determined by many aspects, among which odour and taste are the most important attributes. Odour may be negatively affected by the presence of a pheromonal steroid, androstenone, and a fermentation product of l-tryptophan, skatole. Male pigs are surgically castrated in many countries to minimise the risk of accumulation of high levels of androstenone and skatole. Raising entire male pigs is more profitable because they have superior production characteristics and improved meat quality due to leaner carcasses and higher protein content, as compared to castrated pigs. Furthermore, surgical castration is negative from an animal welfare point of view. In most studies, no differences in sensory quality have been found between lean meat from entire male pigs with low levels of androstenone and skatole and pork from castrates and females. The question that remains is: which substances are responsible for boar taint besides androstenone and skatole and whether they need to be considered? The threshold values used for androstenone and skatole might also be too high for highly sensitive persons. Recent research shows that a human odorant receptor, ORD7D4, is involved in sensitivity to androstenone. If the ORD7D4 genotypes of consumer and expert panels are known, this might facilitate consumer studies in the future. There is still a great need for rapid on/at-line detection methods in abattoirs for identifying carcasses with unacceptable levels of boar taint compounds. Several emerging rapid technologies with a potential for boar taint detection have been investigated. They represent various measurement principles such as chemical sensor arrays (electronic noses), mass-spectrometry fingerprinting, ultra-fast gas chromatography, gas-phase spectrometry and biosensors. An industrial detection method should allow 100% correct classification of both acceptable and not-acceptable samples with regard to boar taint sorting criteria. There are, however, still too high a percentage of false negatives ranging from 5% to 20%. In addition, these methods do not yet seem to fulfil the industrial specifications with regard to cost efficiency, simplicity and analysis time. There is still no dedicated measurement technology available for on/at-line detection of boar-tainted carcasses that measures both androstenone and skatole.